2021
DOI: 10.3390/ijerph182413165
|View full text |Cite
|
Sign up to set email alerts
|

Digital Intervention for Problematic Smartphone Use

Abstract: Smartphones have become the primary devices for accessing the online world. The potential for smartphone use to become problematic has come into increasing focus. Students and young adults have been shown to use their smartphones at high rates and may be at risk for problematic use. There is limited research evaluating interventions for problematic smartphone use. The present research aimed to develop and evaluate a digital intervention for problematic smartphone use in a student population. A mixed-method cas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 37 publications
1
13
0
Order By: Relevance
“…Eight studies (ten arms) reported the delivery of cognitive restructuring [ 45 , 51 , 54 , 55 ], cognitive bias modification (CBM) [ 47 , 50 ], exposure therapy [ 49 ], or mindfulness [ 53 ]. Cognitive restructuring prompted participants to identify, challenge, and replace automatic negative thoughts associated with gaming, gambling, pornography, and nonspecified internet use.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Eight studies (ten arms) reported the delivery of cognitive restructuring [ 45 , 51 , 54 , 55 ], cognitive bias modification (CBM) [ 47 , 50 ], exposure therapy [ 49 ], or mindfulness [ 53 ]. Cognitive restructuring prompted participants to identify, challenge, and replace automatic negative thoughts associated with gaming, gambling, pornography, and nonspecified internet use.…”
Section: Resultsmentioning
confidence: 99%
“…Five studies (five arms) reported the delivery of stimulus control [ 46 , 53 , 56 ], behavioral substitution [ 45 ], or self-monitoring [ 45 , 48 ], and five studies (five arms) delivered social support [ 45 , 48 , 52 , 54 , 55 ]. Stimulus control involved periods of exclusion from online gambling venues or reducing prompts, inclusive of removing notifications, placing the phone out of sight, or turning it off and establishing phone-free periods during the day (eg, before sleep).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Today’s mobile phone has many features besides talking or sending messages. All its possibilities are making people more and more attracted to the benefits of the digital world, regardless of the risks they may cause [ 1 , 2 ].…”
Section: Introductionmentioning
confidence: 99%